Effect of polarization scan rate on corrosion in acidic solution to the properties of Sn-Cu solder - Low, Suk Yen (School of Materials Engineering, University Malaysia Perlis, 2016)
The objectives of this project are to investigate the effect of polarization scan rate on corrosion in acidic solution to the effect properties of Sn-Cu solder, to characterize the corrosion properties of Sn-Cu solder in acidic solution at different polarization scan rate through polarization curves and to investigate the structural, morphological and elemental characterizations of Sn-Cu free solder alloy